1983
DOI: 10.1002/ajmg.1320140413
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and frequency of X‐linked conditions in a cohort of moderately retarded males with affected brothers

Abstract: An epidemiological study was carried out on the group of moderately retarded brothers (IQ, 30-55) identified by Turner and Turner [1974]. Of the original 58 sets of brothers, 54 sets (now 17 to 32 years old) were traced; another four sets (missed in the earlier survey) were added. Forty-five of the 58 pairs were diagnosed as having nonspecific X-linked mental retardation (MR) giving an overall frequency of 5.57 moderately retarded males/10,000 male births. In 12 of the 45 families, affected males had the fragi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
1
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 12 publications
(4 reference statements)
2
46
1
1
Order By: Relevance
“…These pooled data suggest that the proportion of monogenic XLMR in sporadic MR males would be at best 10% (Table 1). Indeed, this would fit with the data on affected male sibpairs of Fishburn et al, 3 as the proportion of non-fragile X to fragile X sibpairs was about 3 to 1, and, given the incidence of fragile X mutation (2 -2.5% of MR males), this would suggest an incidence of 6 -8% for nonfragile X XLMR in nonsyndromic (or at least nonclearly syndromic) patients.…”
supporting
confidence: 66%
“…These pooled data suggest that the proportion of monogenic XLMR in sporadic MR males would be at best 10% (Table 1). Indeed, this would fit with the data on affected male sibpairs of Fishburn et al, 3 as the proportion of non-fragile X to fragile X sibpairs was about 3 to 1, and, given the incidence of fragile X mutation (2 -2.5% of MR males), this would suggest an incidence of 6 -8% for nonfragile X XLMR in nonsyndromic (or at least nonclearly syndromic) patients.…”
supporting
confidence: 66%
“…Epidemiological studies repeatedly showed a sex bias, with 30 -50% excess of males over females, and led to the assumption that much of the excess of male MR may be due to X-linked genes. 7,10,11 If monogenic XLMR was to account for an excess of 30% of mentally retarded males over females, one would expect that 20 -25% of genetically based MR in males, including sporadic MR cases, are caused by XLMR genes (see also Supplementary information S2 in Ropers and Hamel 5 ). However, recent molecular studies, 12,13 in combination with clinical follow-up of a large cohort of patients, 7 are suggesting that the proportion of monogenic XLMR in sporadic MR males would account at best for 8 -10% of the genetic causes of MR. More generally, this new revision of estimates downwards and the recent progress in genetic counseling and prenatal diagnosis of specific MR conditions such as fragile X syndrome, as well as the lack of data concerning the prevalence of autosomal causes justify achievement of further epidemiological studies on MR.…”
Section: Definitionmentioning
confidence: 99%
“…Patients with MRX only have reduced mental capacities, whereas patients with MRXS have additional clinically recognizable features, such as neuromuscular abnormalities, dysmorphisms and congenital malformations. On average one in every 600 males has XLMR [Herbst and Miller, 1980;Roeleveld et al, 1997;Leonard and Wen, 2002] and about two thirds of these patients are thought to be nonsyndromic [Fishburn et al, 1983]. Currently, 25 genes are known to be involved in MRX and 42 genes in MRXS (http://xlmr.interfree.it/home.htm).…”
Section: Introductionmentioning
confidence: 99%